Technology Transfer in Biotechnology : A Global perspective - Ganguli, Prabuddha; Ed (Wiley-VCH, 2009)
Here, the world's top experts impart their knowledge and experience, many in print for the first time. By considering developing country markets, this book is the first truly global guide to technology transfer, helping companies all around the world to a.